Glyceraldehyde-3-Phosphate Dehydrogenase Mediates Anoxia Response and Survival in Caenorhabditis elegans - Mendenhall, Alexander R. (Copyright © 2006 by the Genetics Society of America, 2006)
Oxygen deprivation has a role in the pathology of many human diseases. Thus it is of interest in understanding the genetic and cellular responses to hypoxia or anoxia in oxygen-deprivation-tolerant organisms such as Caenorhabditis elegans. In C. elegans the DAF-2/DAF-16 pathway, an IGF-1/insulin-like signaling pathway, is involved with dauer formation, longevity, and stress resistance. In this report we compared the response of wild-type and daf-2(e1370) animals to anoxia. Unlike wild-type animals, the daf-2(e1370) animals have an enhanced anoxia-survival phenotype in that they survive long-term anoxia and high-temperature anoxia, do not accumulate significant tissue damage in either of these conditions, and are motile after 24 hr of anoxia. RNA interference was used to screen DAF-16-regulated genes that suppress the daf-2(e1370)-enhanced anoxia-survival phenotype. We identified gpd-2 and gpd-3, two nearly identical genes in an operon that encode the glycolytic enzyme glyceraldehyde-3-phosphate dehydrogenase. We found that not only is the daf-2(e1370)-enhanced anoxia phenotype dependent upon gpd-2 and gpd-3, but also the motility of animals exposed to brief periods of anoxia is prematurely arrested in gpd-2/3(RNAi) and daf-2(e1370);gpd-2/3(RNAi) animals. These data suggest that gpd-2 and gpd-3 may serve a protective role in tissue exposed to oxygen deprivation.